Multiple hydatid cyst disease revealed by an expansive intracranial process: A case report - Salwa Nechi; Ghada Gharbi; Amel Douggaz; Houda Belfekih; Abir Chaabane; Mohamed Karim Mfarrej; Emna Chelbi (Clinical Case Reports)
Abstract Hydatid disease is a real public health problem in developing countries. Cerebral localization is rare; it does not exceed 2%. It is more frequent in children and adolescents. It is often primary in children. In adults, it is less frequent and generally associated with other localizations. We report the case of a 60‐year‐old Tunisian patient with pulmonary, hepatic and cerebral hydatid cyst, revealed by neurological symptoms with an expansive intracranial process on brain imaging.